Donated Human Milk as a Determinant Factor for the Gut Bifidobacterial Ecology in Premature Babies - Arboleya, Silvia (Microorganisms, 2020)
Correct establishment of the gut microbiome is compromised in premature babies, with Bifidobacterium being one of the most affected genera. Prematurity often entails the inability to successfully breastfeed, therefore requiring the implementation of other feeding modes; breast milk expression from a donor mother is the recommended option when their own mother’s milk is not available. Some studies showed different gut microbial profiles in premature infants fed with breast milk and donor human milk, however, it is not known how this affects the species composition of the genus Bifidobacterium. The objective of this study was to assess the effect of donated human milk on shaping the gut bifidobacterial populations of premature babies during the first three months of life. We analyzed the gut bifidobacterial communities of 42 premature babies fed with human donor milk or own-mother milk by the 16S rRNA–23S rRNA internal transcriber spaces (ITS) region sequencing and q-PCR. Moreover, metabolic activity was assessed by gas chromatography. We observed a specific bifidobacterial profile based on feeding type, with higher bifidobacterial diversity in the human donor milk group. Differences in specific Bifidobacterium species composition may contribute to the development of specific new strategies or treatments aimed at mimicking the impact of own-mother milk feeding in neonatal units.